2014
DOI: 10.1175/jtech-d-13-00086.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing State of Submicrometer Sea Spray Particles Enriched by Insoluble Species in Bubble-Bursting Experiments

Abstract: Measurements of size distribution, hygroscopicity, and volatility of submicrometer sea spray particles produced by the bubble busting of artificial and natural seawater were conducted to determine their mixing state and volume fractions of hygroscopic and nonhygroscopic species or volatile and nonvolatile species. The particles sprayed from artificial seawater having insoluble silica particles were found to be an external mixture of two groups of particles having hygroscopic growth factors (HGFs) of 1.33 (an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 52 publications
(75 reference statements)
0
30
2
Order By: Relevance
“…This method of enriching the seawater with organic matter allows for natural dynamic ecosystem processes to shape the composition of the organic matter in the seawater, similar to the types of interactions found in natural phytoplankton blooms (Azam and Malfatti, 2007;Pomeroy et al, 2007;Teeling et al, 2012). While the total chlorophyll a concentration in these experiments is an indirect indicator of the autotrophic biomass, it is notable that various controlled SSA generation studies have shown that the amount of organic matter imparted to SSA is only a weak function of the seawater chlorophyll concentration, and depends instead on the amount and composition of organic matter in the seawater Collins et al, 2013;Prather et al, 2013;Park et al, 2014;Quinn et al, 2014). Total organic carbon (TOC) concentrations in the seawater were measured by means of the high temperature combustion method (Shimadzu Scientific Instruments) after acidifying the sample with 12N hydrochloric acid.…”
Section: Foam Production Experimentsmentioning
confidence: 54%
See 2 more Smart Citations
“…This method of enriching the seawater with organic matter allows for natural dynamic ecosystem processes to shape the composition of the organic matter in the seawater, similar to the types of interactions found in natural phytoplankton blooms (Azam and Malfatti, 2007;Pomeroy et al, 2007;Teeling et al, 2012). While the total chlorophyll a concentration in these experiments is an indirect indicator of the autotrophic biomass, it is notable that various controlled SSA generation studies have shown that the amount of organic matter imparted to SSA is only a weak function of the seawater chlorophyll concentration, and depends instead on the amount and composition of organic matter in the seawater Collins et al, 2013;Prather et al, 2013;Park et al, 2014;Quinn et al, 2014). Total organic carbon (TOC) concentrations in the seawater were measured by means of the high temperature combustion method (Shimadzu Scientific Instruments) after acidifying the sample with 12N hydrochloric acid.…”
Section: Foam Production Experimentsmentioning
confidence: 54%
“…These studies produce SSA from disintegrating foam in natural seawater or proxy materials mainly by means of sintered glass bubblers or plunging water jets. (Sellegri et al, 2006;Keene et al, 2007;Tyree et al, 2007;Fuentes et al, 2010b;Hultin et al, 2010;Bates et al, 2012;Park et al, 2014). Since it is well known that SSA is produced by the bursting of air bubbles at the sea surface (e.g., Blanchard and Woodcock, 1957;Lewis and Schwartz, 2004;de Leeuw et al, 2011), the differences between generation methods for SSA in the laboratory differ primarily by the method of bubble production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the transfer of insoluble species has been examined in the past, 48 concentration and emission of graphitic carbon from the SSML is a unique observation with implications for radiative transfer and carbon cycling between the ocean and the atmosphere.…”
Section: Reduced Aliphatic and Graphitic Carbonmentioning
confidence: 99%
“…[15] Sea spray aerosol has been shown to comprise more than just sodium chloride; it contains other inorganic salts as well as biologically produced organic species. [16] While the majority of submicrometre SSA particles contain mostly sea salts (i.e. NaCl, KCl, MgCl 2 and CaCl 2 ), SSA particles contain increasing levels of organic species (relative to inorganic species) as particle diameter decreases to submicrometre sizes.…”
Section: Introductionmentioning
confidence: 99%